2017
DOI: 10.1002/er.3941
|View full text |Cite
|
Sign up to set email alerts
|

Performance of an environmentally benign acid base flow battery at high energy density

Abstract: SummaryAn increasing fraction of energy is generated by intermittent sources such as wind and sun. A straightforward solution to keep the electricity grid reliable is the connection of large-scale electricity storage to this grid. Current battery storage technologies, while providing promising energy and power densities, suffer from a large environmental footprint, safety issues, and technological challenges. In this paper, the acid base flow battery is re-established as an environmental friendly means of stor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(49 citation statements)
references
References 54 publications
0
49
0
Order By: Relevance
“…When a sufficient electric field is applied, the BPM dissociates water into OHand H + , producing a controllable ∆pH over the membrane as shown in Figure (10a) and b [85][86][87][88][89][90]. Using a bipolar membrane, the thermodynamic minimum voltage required for this water dissociation is 0.829 volts for a produced ∆pH = 14.…”
Section: Bipolar Membrane Electrodialysis (Bpmed)mentioning
confidence: 99%
“…When a sufficient electric field is applied, the BPM dissociates water into OHand H + , producing a controllable ∆pH over the membrane as shown in Figure (10a) and b [85][86][87][88][89][90]. Using a bipolar membrane, the thermodynamic minimum voltage required for this water dissociation is 0.829 volts for a produced ∆pH = 14.…”
Section: Bipolar Membrane Electrodialysis (Bpmed)mentioning
confidence: 99%
“…Current commercial membranes are designed only for dissociating water, while operating BPMs under water recombination (which occurs during the discharging process in the ABFB), has been so far overlooked by membrane scientists and manufacturers. Hence, when using commercial BPMs in ABFB the discharge current densities of the battery are today limited by membrane delamination [ 25 , 30 ], and are thus relatively low. In particular, van Egmond et al reported successful stable performance (up to 9 cycles) for a 1 M HCl-1 M NaOH battery operated at 15 A/m 2 discharge current density [ 25 ], while Xia et al noted water accumulation in the BPM junction when operating a 0.75 M HCl–0.75 M NaOH battery at discharge current densities above 200 A/m 2 [ 30 ].…”
Section: Battery Components and Designmentioning
confidence: 99%
“…The electrode compartments can be rinsed with a different solution, for example Na 2 SO 4 [ 30 ], to avoid the production of Cl 2 at the anode (i.e., the oxidation product when using only NaCl solutions at the electrodes). The electrodes do not necessarily need to be of metal, but can also be of more environmentally friendly carbon material [ 25 ], in which case an electrode rinse solution with a redox couple must be used. Using such electrode rinse solution has the advantage of opposite electrode reactions occurring at the anode and cathode, meaning that by recirculating the rinse solution no net change of the chemical composition occurs, and the thermodynamic voltage of the electrode reactions is zero.…”
Section: Battery Components and Designmentioning
confidence: 99%
See 2 more Smart Citations